Proteasome Activity and C-Reactive Protein Concentration in the Course of Inflammatory Reaction in Relation to the Type of Abdominal Operation and the Surgical Technique Used. (14th October 2018) - Tylicka, Marzena; Matuszczak, Ewa; Karpińska, Maria; Hermanowicz, Adam; Dębek, Wojciech; Ostrowska, Halina
Abstract : Surgical tissue damage and the accompanying inflammatory response lead to proteasome activation, initiation of damaged protein degradation, and induction of acute-phase inflammatory response. The aim of this study was to investigate the rate of change in proteasome chymotrypsin-like (ChT-L) activity and C-reactive protein concentration depending on the degree of tissue damage and their correlation with prealbumin concentrations in children before and after abdominal surgery. This experimental study included children who underwent abdominal surgery between 2015 and 2017. Plasma prealbumin concentrations and C-reactive protein levels (CRP) were determined by standard biochemical laboratory procedures. Proteasome activity was assessed using a Suc-Leu-Leu-Val-Tyr-AMC peptide substrate. Elevation of plasma proteasome activity was noted in children after laparoscopic and open abdominal surgeries. However, 20S proteasome activity in children undergoing conventional open surgery was significantly higher (P < 0.05 ) than in patients subjected to laparoscopy. At the same time, an increase in the CRP level was observed. However, there was no correlation between C-reactive protein concentrations and the type of abdominal surgery while there was a correlation observed in the case of proteasomes. Proteasome activity correlates with the degree of surgical tissue damage and prealbumin concentrations. More invasive surgery leads to a stronger activation of the proteasome involved in removing proteins that were damaged due to the surgical procedure. Proteasomes are more specific markers because there is a correlation between proteasome activity and the type of abdominal surgery in contrast to C-reactive protein concentrations which are not different in response to surgery performed in regard to ovarian cysts or cholelithiasis.